Brand Image, Service Quality And Patient Satisfaction On Patient Loyalty - Andi Ajmal; Muh Yusuf Q; M. Risal (Jurnal Mantik, 2022)
This study aims to describe and analyze the effect of the surgical polyclinic image mouth hospital Sawerigading City Palopo, quality service and satisfaction patient on patient loyalty. There are three hypotheses that were tested by path analysis using the least squares instrument partially. The population in this study was 100 patients who had visited, the population was also a sample. Data were collected using a questionnaire with a purposive sampling technique by combining Quota Sampling and Accidental Sampling. The research data used SPSS 19 with the results of multiple regression coefficients Y = 1.112 + 0.268X1 - 0.002X2 + 0.246X3. From testing the coefficient of determination (R2), the results obtained R2 of 0.278 (27.80%). It means that 27.80% that the independent variables, namely image, service quality, patient satisfaction have an influence on patient loyalty by 27.8%, while the remaining 72.2% is influenced by other variables not observed in this study. Based on the results of this study, the Oral Surgery Polyclinic at Sawerigading Palopo Hospital needs to continue to improve its image and service quality because it has an influence on patient satisfaction. Significantly increased patient satisfaction increases patient loyalty. These results indicate that the first, second, third hypotheses are accepted. image, service quality, patient satisfaction, collectively affect patient loyalty at the Oral Surgery Polyclinic of Sawerigading Hospital Palopo.